1999
DOI: 10.1046/j.1365-3024.1999.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of malaria transmission‐blocking vaccine candidate, y230.CA14 following crosslinking in the presence of tetanus toxoid

Abstract: Proteolytically processed 310 kDa form of Plasmodium falciparum gamete surface antigen, Pfs230, is the target of malaria transmission-blocking monoclonal antibodies. To design a recombinant malaria transmission-blocking subunit vaccine, the amino terminus of the 310 kDa surface-exposed form of Pfs230 was mapped to amino acids (aa) 522 and 584 using a series of peptides and recombinant proteins encoding distinct regions of Pfs230. Antiserum generated against an Escherichia coli-produced recombinant protein, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recombinant expression of full-length Pfs230 for TBV development has not been successful due to the size and complexity of the protein. Additionally, production of subdomains of Pfs230 in early studies using both E. coli (48) and Saccharomyces cerevisiae (44) has not been successful in forming a correctly folded molecule capable of consistently eliciting a high level of TB antibodies. However, expression of recombinant Pfs230C with TB activity has been achieved by Tachibana et al (40a), who demonstrated TB activity of Pfs230C produced in the wheat germ cell-free expression system.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant expression of full-length Pfs230 for TBV development has not been successful due to the size and complexity of the protein. Additionally, production of subdomains of Pfs230 in early studies using both E. coli (48) and Saccharomyces cerevisiae (44) has not been successful in forming a correctly folded molecule capable of consistently eliciting a high level of TB antibodies. However, expression of recombinant Pfs230C with TB activity has been achieved by Tachibana et al (40a), who demonstrated TB activity of Pfs230C produced in the wheat germ cell-free expression system.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal effective antigenic region of Pfs230 was originally mapped to amino acids 443–1132 referred to as region C, which contains 13 cysteines (Bustamante, 2000). These cysteines need to be properly paired for the epitopes to attain native conformation and elicit full transmission-blocking immunity, making P230 a challenging protein to produce in heterologous expression systems (Riley et al, 1995; Williamson et al, 1995; Vincent et al, 1999; Bustamante et al, 2000; Williamson, 2003; Farrance et al, 2011; Tachibana et al, 2011; Kapulu et al, 2015). However, more recently, the prodomain N-terminal to the first s48/45 domain alone was reported to be sufficient to induce transmission-blocking antibodies (Tachibana et al, 2011).…”
Section: 6-cys Proteins In the Sexual Stagesmentioning
confidence: 99%
“…Pfs230 has been speculated to have a male gamete function because parasites with a truncated form of Pfs230 were shown to adhere to uninfected erythrocytes, even though their capacity to infect mosquitoes was severely decreased by greater than 95% (22). Various forms or domains of Pfs230 have been expressed in several recombinant expression systems, including Saccharomyces cerevisiae, Escherichia coli, plants, and wheat germ (9,12,13,23) but to date none of the recombinant forms of Pfs230 have been suitable for extensive biochemical and biophysical characterization to effectively characterize a functional antibody response. A primary bottleneck in recombinant protein production has been the presence of an unique disulfide bond structure initially modeled by Gerloff et al (24).…”
mentioning
confidence: 99%